Tanggung Jawab PT. Timor Tour & Travel Agen Kupang Terhadap Penumpang Pengguna Jasa Travel - Atika Putri Jayanti; Patricia Abigail Martha Leba; Stefanus Don Rade (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
PT Timor Tour & Travel is one of the travel agency business actors that provides services for transportation services that are responsible for service passengers if things happen that are detrimental to passengers due to negligence committed by the company. In Indonesia itself, Law Number 22 of 2009 concerning Highway Traffic and Transportation has been in force which regulates the responsibilities of business actors in carrying out their business activities. Responsibilities need to be considered because it raises questions about who should be burdened with guilt and to what extent this accountability burden it. So because of that the authors conducted research with the title Responsibilities of PT Timor Tour & Travel Kupang agents for passengers of travel user services. This study aims to identify and explain the implementation of the responsibilities of PT. Timor Tour & Travel Kupang Agent for users of travel services and obstacles from PT. Timor Tour & Travel Agent Kupang in carrying out duties. The approach used is a statutory and contextual approach. The population in this study are managers of PT. Timor Tour & Travel, drivers and users of travel services. The analysis technique used is descriptive qualitative. The results of the research show that the implementation of PT. Timor Travel loads passengers at their destination comfortably and is also happy to be responsible for compensating passengers for user services according to applicable regulations, namely Law NO. 22 of 2009 concerning Highway Traffic and Transportation and the principle of responsibility based on presumption, but the implementation in the field has not been in accordance with the facts and looks more at evidence of losses suffered by passengers. Obstacles in accountability can be seen from poor communication in resolving problems between the PT and the passenger, with the rules made by the PT that do not pay much attention to the losses suffered by the passengers. The conclusion of this study is the implementation of responsibilities in general and compensating for players who are harmed by the company, but the company sees more written evidence of losses suffered by passengers. can solve existing problems. The advice given by the author is that in carrying out the responsibilities of the company, it must carry out according to the rules contained in the UULLJR and the principle of responsibility based on presumption with the burden of proof being reversed. and The troubled parties as well as PT or passengers should have good communication to be able to resolve existing problems. So that there are no obstacles in the implementation of responsibilities.